2020
DOI: 10.1007/s40477-020-00522-2
|View full text |Cite
|
Sign up to set email alerts
|

SIUMB recommendations for focal pancreatic lesions

Abstract: Contrast-enhanced ultrasonography (CEUS) is increasingly being performed in Italy and Europe, particularly in the field of hepato-gastroenterology. Initially, it was mainly carried out to characterize focal hepatic lesions, but, since then, numerous studies have demonstrated its efficacy in the differential diagnosis of focal pancreatic pathologies (D’Onofrio et al. in Expert Rev Med Devices 7(2):257–273, 2010; Vidili et al. in J Ultrasound 22(1):41–51, 2019). The purpose of this paper is to provide Italian Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 31 publications
0
12
0
1
Order By: Relevance
“…D'Onofrion et al [5,41] reported that for PDAC, the diagnostic sensitivity of CEUS was comparable to that of CECT (86.47% vs. 83.58%). Therefore, if conventional ultrasound detects a suspected pancreatic mass, CEUS might be recommended to identify the characteristics of PDAC.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…D'Onofrion et al [5,41] reported that for PDAC, the diagnostic sensitivity of CEUS was comparable to that of CECT (86.47% vs. 83.58%). Therefore, if conventional ultrasound detects a suspected pancreatic mass, CEUS might be recommended to identify the characteristics of PDAC.…”
Section: Discussionmentioning
confidence: 97%
“…[6][7][8][9][10][11][12][13] Contrast-enhanced computed tomography (CECT) and magnetic resonance imaging have been widely used for the preoperative evaluation and post-operative follow-up of pancreatic masses, especially malignant pancreatic tumors; however, limited information regarding the significance of CEUS for patients with PDAC has been reported. [4,5,14,15] One meta-analysis described the overall diagnostic accuracy of CEUS for differentiating PDAC from other pancreatic lesions. [16] Two studies compared the performance of CEUS and CECT for the differential diagnosis of MFP and PDAC; however, these studies were published before 2015 and included 120 samples in total; [7,8] thus, the optimal imaging method in differentiating MFP from PDAC could not be determined.…”
Section: Introductionmentioning
confidence: 99%
“…However, transabdominal US is still used as a first-line screening tool in clinical settings and considered a favourable modality for routine medical examinations of asymptomatic individuals [17]. Compared with baseline US, CEUS has been reported to significantly improve the efficacy of characterising SPLs [8][9][10][11][12] and is recommended for diagnosis of SPLs by established guidelines [1,13]. In the current study, hypoenhancement in both the arterial phase (AP) and venous phase (VP), hyperenhancement or isoenhancement in the AP followed by hypoenhancement in the VP, ill-defined border, and dilated MPD were found to be independent risk factors for MSPLs, which is consistent with the findings of previous studies [18][19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional US is commonly used as a screening tool in the detection and initial assessment of pancreatic lesions, but the diagnostic performance of US reported in the literature for pancreatic cancer varies, with sensitivity and specificity values ranging from 68 to 98% and from 50 to 100%, respectively [5][6][7]. Currently, with the application of contrast agents and low mechanical index real-time harmonic imaging, contrastenhanced ultrasound (CEUS) has been reported to significantly improve the efficacy of US in characterising suspicious pancreatic lesions [8][9][10][11][12] and is recommended for the diagnosis of SPL by guidelines [1,13]. The main advantage of CEUS over other imaging modalities is the high temporal resolution which allows for real-time evaluation of the pancreas.…”
Section: Introductionmentioning
confidence: 99%
“…Zur Evaluation der systemischen Tumorausbreitung kann eine Abdomensonographie sinnvoll sein, wenn keine entsprechende Schnittbildgebung vorliegt, da hier fokale Leberläsionen ein-oder ausgeschlossen werden [159,160]. Der negativ prädiktive Wert einer abdominellen Ultraschalluntersuchung ist bei guten Schallbedingungen sehr hoch und kann als Auschlussdiagnostik bei unklaren Beschwerden gewählt werden.…”
Section: Hintergrundunclassified